Cravings Hungry for more - Teigen, Chrissy (New York : Clarkson Potter/Publishers, 2018)
"This follow-up [to Cravings] takes us further into [Teigen's] kitchen--a kitchen now marked by new parenthood, a need for some quicker meals, and multi-purpose sauces and condiments, without sacrificing any of [her] signature need for maximum flavor. Through 100 full-flavored, family-friendly recipes, Teigen shows how to make cooking part of a stylish-but-busy lifestyle"--
Keywords: Cooking; COOKING / Methods / Quick & Easy; COOKING / Courses & Dishes / General; COOKING / Entertaining; Cookbooks